Sonia Morales Cano, Escultura funeraria gótica. Castilla-La Mancha. Madrid: Silex Ediciones, 2017. ISBN 978-84-7737-667-5. - Prieto López, Diego (De Medio Aevo, 2020)
Reseña de la obra de Sonia Morales Cano, Escultura funeraria gótica. Castilla-La Mancha. Madrid: Silex Ediciones, 2017. ISBN 978-84-7737-667-5.